THE EFFECT OF APPLYING THINK-TALK-WRITE STRATEGYON STUDENTS’ ACHIEVEMENT IN WRITING ANALYTICAL EXPOSITION TEXT - Irna Junita and Rahmah (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2015)
This study deals with The Effect of Applying Think-Talk-Write Strategy on the Students’ Achievement in Writing Analytical ExpositionText. The method of the research was quasi experimental design. The population of the research was grade XI of SMA Swasta Al-Fattah Medan. There were two classes namely XI IPA 1 and XI IPA 2 and each class consist of 30 students with the total number 60 students. This study uses total sample which these two classes were chosen as sampling.XI IPA 1 as the experimental group and XI IPA 2as the control group. The experimental group was taught by applying Think-Talk-Write Strategy and the control group without applying Think-Talk-Write Strategy. The data were acquired by administrated the pre – test and the post – test. The mean score of the experimental group in pre – test = 57.7, Control Group = 57.53. In the post – test, mean score of the experimental group = 67.53 , while the control group = 63.7